High power λ ~ 8.5 μm quantum cascade laser grown by MOCVD operating continuous-wave up to 408 K. (November 2021) - Fei, Teng; Zhai, Shenqiang; Zhang, Jinchuan; Zhuo, Ning; Liu, Junqi; Wang, Lijun; Liu, Shuman; Jia, Zhiwei; Li, Kun; Sun, Yongqiang; Guo, Kai; Liu, Fengqi; et al.
Abstract: Robust quantum cascade laser (QCL) enduring high temperature continuous-wave (CW) operation is of critical importance for some applications. We report on the realization of lattice-matched InGaAs/InAlAs/InP QCL materials grown by metal-organic chemical vapor deposition (MOCVD). High interface quality structures designed for light emission at 8.5 μ m are achieved by optimizing and precise controlling of growth conditions. A CW output power of 1.04 W at 288 K was obtained from a 4 mm-long and 10 μ m-wide coated laser. Corresponding maximum wall-plug efficiency and threshold current density were 7.1% and 1.18 kA/cm 2, respectively. The device can operate in CW mode up to 408 K with an output power of 160 mW.